2017
DOI: 10.1016/j.envdev.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for sustainable nutrient management: insights from a mixed natural and social science analysis of Chinese crop production systems

Abstract: [148 words]In China intensification of agriculture has been achieved at a cost to the environment. The extension service is the leading public resource to address this but remains focused by a historic national ethos for food security, production and economic growth, whilst its administrative structure is hierarchical, slow to change and lacking in relevant functional integration. Investigation of three case study farming systems identifies how to rebalance productivity with stewardship of farm inputs and natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition, climate changes and man-made interventions lead to sharp decline in fertile soil and suitable conditions for food crop production (Khan and Akhtar 2015;Chen et al 2017). Also traditional methods used for irrigation, fertilization and other agricultural processes may increase this problem due to the accumulation and uncontrolled transformation of added materials (Bellarby et al 2016;van der Laan et al 2017). One of the solutions for this problem is the use of new technologies in irrigation and fertilization and search for less toxic forms for plant nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, climate changes and man-made interventions lead to sharp decline in fertile soil and suitable conditions for food crop production (Khan and Akhtar 2015;Chen et al 2017). Also traditional methods used for irrigation, fertilization and other agricultural processes may increase this problem due to the accumulation and uncontrolled transformation of added materials (Bellarby et al 2016;van der Laan et al 2017). One of the solutions for this problem is the use of new technologies in irrigation and fertilization and search for less toxic forms for plant nutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that nutrient surpluses in the soil of both two counties have increased significantly since 1992 (Fig. 2) due to the rapidly increasing application of synthetic fertilizers in China since the 1980s (Bellarby et al, 2017;Sun et al, 2020;Yu et al, 2020). N and P surpluses of the two counties are higher than that of other studies.…”
Section: High Surplus and Low Nue At Intensive Orchard Regionmentioning
confidence: 48%
“…Maize (Zea mays L.) is a crucial crop for global food security, and China is the worldly 2nd-largest producer of maize crop with approximately 43.55 million hectares of cultivated land, accounting for 36.8% of the country's grain acreage and 39.9% of its production (Manevski et al, 2016;Bai et al, 2021;Nbs, 2021). While maize is the primary summer crop in northern China, and it faces challenges such as excessive nitrogen and phosphorus input, low yield, water waste, and environmental pollution etc (Bellarby et al, 2017;Wang et al, 2022d).…”
Section: Introductionmentioning
confidence: 99%